Penerapan Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas Publik (SAK ETAP) Terhadap Laporan Keuangan (Studi Kasus CV. Finopi Indonesia) - Tania, Elsa Trisna; Akhirruddin, Anita (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This study aims to evaluate the implementation of SAK ETAP in the financial statements of CV. Finopi Indonesia and identify the challenges faced by the company in the process. This study uses a qualitative descriptive method using a case study approach. Data collection techniques through data triangulation, namely interviews, documentation, and observation. The results of the study in indicate that CV. Finopi Indonesia has not fully implemented SAK ETAP, by only preparing basic financial statements such as general ledgers and cash flow statements. Significant obstacles faced are the absence of SOPs regarding the writing of financial statements, the company has not paid attention to the accounting cycle, limited human resources, early readiness, the need for external support, and considerations of costs and impacts. This study is limited to one entity, so the result cannot be generalized to other entities. The implications of this study are important for small and medium-sized companies in Indonesia to improve transparency and accountability by complying with applicable accounting standards, and providing insight into the development of accounting policies the small and medium-sized company sector.